Porcine Circovirus-Like Virus P1 Inhibits Wnt Signaling Pathway in Vivo and in Vitro - Zhu, Xuejiao; Wen, Libin; Sheng, Shaoyang; Wang, Wei; Xiao, Qi; Qu, Meng; Hu, Yiyi; Liu, Chuanmin; He, Kongwang (Frontiers in Microbiology, 2018)
Porcine circovirus-like virus P1 is an important pathogen of the current pig industry, the infection mechanism is not entirely clear. Wnt signaling pathway plays an important role in the growth of young animals and infection of some viruses. This study was designed to demonstrate the effects of P1 infection on the Wnt signaling pathway. In vivo experiments, we demonstrated the down-regulatory effects of P1 infection in piglets and mice on the downstream components expression levels of Wnt signaling pathway, and the effects of Wnt signaling pathway activation on the pathogenesis of P1. In vitro studies, we found P1 infection down-regulated protein level of β-catenin and mRNA level of mmp2, prevented the β-catenin from entering into nucleus, abolished the TCF/LEF promoter activity, proved that P1 could inhibit the activation of Wnt signaling pathway in vitro. Finally we found that VP1 of P1 virus also had the inhibitory effects on Wnt signaling pathway in vitro, elucidated the mechanism of P1’s inhibitory effects on the Wnt signaling pathway and offered the possibility that the suppression of Wnt signaling pathway was involved in the post-weaning multisystemic wasting syndrome (PMWS), laying a foundation for elucidating the pathogenesis of P1.